The Aftermath of Johnson–Reed: John F. Montgomery and Jewish Immigration from Hungary in the 1930s - Zoltán Peterecz (Hungarian Cultural Studies)
The Johnson-Reed Law was a milestone in the history of immigration to the United States, and has been analyzed from various angles, especially how the legal measure dramatically decreased the inflow of immigrants from these places. The article investigates how one American minister in Hungary, John F. Montgomery (1933–1941), reacted and dealt with the new measure. From the mid-1930s in particular, the number of Hungarian Jewish people who wanted to immigrate to the United States grew, which caused frustration to the then American minister in Budapest. Therefore, a closer examination will be made of Montgomery’s work and attitude regarding would-be Jewish immigrants. This case study will broaden our understanding of the aftermath of the Johnson-Reed Law of 1924.